Kegiatan Bimbingan Belajar dalam Meningkatkan Minat Belajar Siswa dengan Media Pembelajaran - Januaris Pane; Riossally Marselina Tumanggor; Bajongga Silaban; Asnida Asnida; Sarinaiba Situmeang; Nanny Natania Lumbantobing (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Tutoring plays a very important role in the development of student learning, because not only what is obtained at school, but learning outside school hours has a large enough impact and has an effect on student interest in learning. Tutoring that is carried out can help students achieve optimal development, so as not to hinder student development. Students whose development is hampered or disturbed will affect their development or learning abilities. We use this method of service activities directly and interview science teachers. This service activity is carried out by applying face-to-face tutoring by conducting learning related to simple practicum using learning media. The results of this tutoring activity motivate students in learning and increase student interest in learning to become more creative and active individuals.